ONTOLOGY-DRIVEN TOOL FOR UTILIZING PROGRAMMING STYLES - Sidorov, Nikolay; Sidorova, Nika; Pirog, Alexander (Proceedings of National Aviation University, 2017)
Activities of a programmer will be more effective and the software will be more understandable when within the process of software development, programming styles (standards) are used, providing clarity of software texts. Purpose: In this research, we present the tool for the realization of new ontology-based methodology automated reasoning techniques for utilizing programming styles. In particular, we focus on representing programming styles in the form of formal ontologies, and study how description logic reasoner can assist programmers in utilizing programming standards. Our research hypothesis is as follows: ontological representation of programming styles can provide additional benefits over existing approaches in utilizing programmer of programming standards. Our research goal is to develop a tool to support the ontology-based utilizing programming styles. Methods: ontological representation of programming styles; object-oriented programming; ontology-driven utilizing of programming styles. Results: the architecture was obtained and the tool was developed in the Java language, which provide tool support of ontology-driven programming styles application method. On the example of naming of the Java programming language standard, features of implementation and application of the tool are provided. Discussion: application of programming styles in coding of program; lack of automated tools for the processes of programming standards application; tool based on new method of ontology-driven application of programming styles; an example of the implementation of tool architecture for naming rules of the Java language standard.